DEVELOPMENT OF HEAVY INDUSTRIES IN THE SOUTHERN PROVINCE OF UZBEKISTAN: HISTORICAL ANALYSIS AND CONSEQUENCES (1930-1960) - Mamatqulov Bekzod Sherozovich (TADQIQOTLAR, 2025)
ABSTRACT: In this article, the development of heavy industries in the southern regions  of  Uzbekistan,  conflicting  situations  in  the  process  of  training  industry personnel are analyzed historically based on scientific sources.